Out-of-hospital cardiac arrest (OHCA) in Bosnia and Herzegovina in the period 2018 -2022: current trends, usage of automated external defibrillators (AED) and bystanders’ involvement - Armin Šljivo; Tatjana Jevtić; Selma Terzić-Salihbašić; Arian Abdulkhaliq; Leopold Reiter; Faris Salihbašić; Ajla Bečar-Alijević; Adin Alijević; Ilma Dadić; Fatima Gavrankapetanović (Medicinski glasnik, 2024)
Aim: To investigate out-of-hospital cardiac arrest (OHCA) trend, provided advanced life support (ALS) measures, automated external defibrillator (AEDs) utilization and by-standers involvement in cardiopulmonary resuscitation (CPR) during OHCA incidents. Methods: This cross-sectional study encompassed data pertaining to all OHCA incidents attended to by the Emergency Medical Service of Canton Sarajevo, Bosnia and Herzegovina, covering the period from January 2018 to December 2022. Results: Among a total of 1131 OHCA events, 236 (20.8 %) patients achieved return of spontaneous circulation (ROSC); there were 175 (74.1%) males and 61 (25.9%) females. The OHCA incidence was 54/100.000 inhabitants per year. After a 30-day period post-ROSC, 146 (61.9%) patients fully recovered, while 90 (38.1%) did not survive during this timeframe. Younger age (p<0.05), initial rhythm of ventricular fibrillation (VF) or pulseless ventricular tachycardia (VT) (p<0.05) and faster emergency medical team (EMT) response time (p<0.05) were significantly associated with obtaining ROSC. Only 38 (3.3%) OHCA events were assisted by bystanders, who were mostly medical professionals, 25 (65.7%), followed by close family members, 13 (34.3%). There was no report of AED usage. Conclusion: This follow-up study showed less ROSC achievement, similar bystanders’ involvement, similar factors associated with achieving ROSC (age, EMT response time) and a decline in OHCA events (especially in year 2021 and 2022) comparing to our previous study (2015-2019). There was an extremely low rate of bystander engagement and no AEDs usage. Governments and health organizations must swiftly improve public awareness, promote better practice (basic life support), and actively encourage bystander participation.
Keywords: cardiopulmonary resuscitation; car-diac events; resus-citation; return of spontaneous circu-lation